Recursos expresivos en el desarrollo de la inteligencia lingüística en niños de 4 a 5 años en educación inicial de la Unidad Educativa “Verbo Divino” provincia Bolívar, cantón Guaranda, periodo académico 2025. - Caza Guano, Andrea Josette (2025)
This study, titled “Expressive Resources in the Development of Linguistic Intelligence in 4- to 5-Year-Old Children in Early Childhood Education at Unidad Educativa ‘Verbo Divino,’ Bolívar Province, Guaranda Canton, Academic Year 2025”, analyzes the role of expressive resources in fostering linguistic intelligence in early childhood. Language, as a cornerstone of children’s holistic development, organizes thought, builds identity, and enables communication. However, in the Ecuadorian educational context—specifically at Unidad Educativa “Verbo Divino”—teaching practices reveal limited use of expressive strategies, reducing opportunities for meaningful language stimulation. Expressive resources such as dramatized stories, oral games, songs, puppets, rhymes, poems, and artistic activities provide children with playful and creative ways to explore language. They encourage confidence, social interaction, verbal fluency, and vocabulary expansion. Despite their pedagogical value, classroom practices are still dominated by traditional methods, which restrict children’s capacity to structure ideas and develop communicative skills effectively. The main objective of this research was to identify expressive resources that promote the development of linguistic intelligence in children aged 4 to 5. A mixed-methods approach was applied, combining qualitative techniques (classroom observation) with quantitative instruments (teacher surveys) to ensure a comprehensive analysis.